Arthur Hugh Clough’s Theory of Political Economy: Challenging Economic Dogmas: Arthur Hugh Clough and His Theory of Political Economy (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Clough attempted to combat some of the ruling economic dogmas of his time. He went a step further than Carlyle in respect of his interest in political economy. He attempted to combat some of the ruling economic dogmas of his time. In July 1844 he said“I am considerably inclined to set to work at Political Economy, for the benefit of the rising generation and to see if I cannot prove ‘the Apostle of Anti-Laisses-faire”.